Alumina powder, resin composition, and adhesive

The use of alumina powder with specific particle size and surface area in a resin composition enhances thermal conductivity and shear bonding strength, addressing the thermal management and adhesion issues in electronic devices.

JP2025070371APending Publication Date: 2025-05-02DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023180634
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing adhesives used in electronic devices lack sufficient thermal conductivity and shear bonding strength, which hampers effective heat dissipation and reliability of electronic components.

Method used

Development of an alumina powder with a specific particle size distribution (D50 between 10 μm and 70 μm) and high specific surface area (greater than 0.23 m²/g) that is used to create a resin composition with enhanced thermal conductivity and shear bonding strength.

Benefits of technology

The alumina powder-based resin composition achieves thermal conductivity greater than 2.3 W/m·K and shear adhesion strength greater than 0.23 MPa, effectively addressing the thermal management and adhesion challenges in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070371000001
    Figure 2025070371000001
  • Figure 2025070371000002
    Figure 2025070371000002
Patent Text Reader

Abstract

To provide alumina powder which gives a resin composition showing good thermal conductivity and good shear adhesive strength.SOLUTION: Alumina powder has a volume-based cumulative 50% diameter D50 of 10 μm or more and 70 μm or less, and a specific surface area by BET method of more than 0.23 m2 / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an alumina powder, a resin composition, and an adhesive. [Background technology]

[0002] Electrical and electronic devices are becoming more and more sophisticated and dense. This has led to a demand for measures to prevent heat generation from electronic components mounted on circuit boards. Heat is conducted from an electronic component to an adjacent component through the adhesive sites between multiple adjacent electronic components in an electronic device, and this heat conduction dissipates heat from the electronic device. For thermal management of electronic devices, it is desirable for the adhesives that bond electronic components to have good thermal conductivity. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-77123 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide an alumina powder that provides a resin composition exhibiting good thermal conductivity and good shear adhesive strength. [Means for solving the problem]

[0005] The present disclosure includes the following aspects. [1] The volume-based cumulative 50% diameter D50 is 10 μm or more and 70 μm or less, and the specific surface area by the BET method is 0.23 m 2 / g or more, alumina powder. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide an alumina powder that provides a resin composition exhibiting good thermal conductivity and good shear bond strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, one embodiment of the present disclosure will be described in detail, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made without departing from the spirit of the present disclosure. Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. Each configuration and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of configurations are possible as appropriate without departing from the spirit of this disclosure. In addition, when multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​among these upper and lower limit values ​​can be combined to form a suitable numerical range. In addition, the lower and / or upper limit values ​​of the numerical range described in this disclosure may be replaced with numerical values ​​within the numerical range and shown in the examples. The expression "X to Y" indicating a numerical range means "X or more and Y or less". When a specific description described for one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments. Unless otherwise specified, all numbers expressing features, items, amounts, parameters, characteristics, periods, etc. used in the specification and claims are understood to be modified in all cases by the term "about". As used herein, the term "about" means that the feature, item, amount, parameter, characteristic, or period so specified encompasses a range above and below the stated feature, item, amount, parameter, characteristic, or period value plus or minus 10 percent. At least, without limiting the application of the doctrine of equivalents to the scope of the claims, each numerical indicator should be interpreted in light of the number of reported significant digits and by applying ordinary rounding techniques. Any numerical range or value inherently includes a range of error necessarily resulting from the standard deviation found in their respective testing measurements. Unless otherwise specified, each individual value of a numerical range herein is incorporated herein as if it were individually recited herein.

[0008] [Alumina powder] The alumina powder according to this embodiment is The volume-based cumulative 50% diameter D50 is 10 μm or more and 70 μm or less, The specific surface area according to the BET method is 0.23 m 2 / g or more.

[0009] Alumina powders designed in this manner can provide compositions with good thermal conductivity and / or good shear bond strength.

[0010] "Volume-based cumulative 50% diameter D50" (hereinafter simply referred to as "D50") refers to the particle diameter (D50) at which the cumulative value corresponds to 50% in the volume-based cumulative particle size distribution measured using a laser diffraction particle size distribution analyzer. The cumulative particle size distribution is expressed by a distribution curve with the particle size (μm) on the horizontal axis and the cumulative value (%) on the vertical axis.

[0011] The "volume-based frequency particle size distribution" is measured by a laser diffraction light scattering method (refractive index: 1.68) and is represented by a distribution curve with the horizontal axis representing particle size (μm) and the vertical axis representing volume-based frequency (%). The alumina powder according to this embodiment has at least two peaks in the volume-based frequency particle size distribution. The peaks may have shoulders. The "particle size" is the value shown on the horizontal axis of the volume-based frequency particle size distribution. "Peak" means a distribution curve that has one maximum in the volume-based frequency particle size distribution. A "shoulder" is an incomplete peak that is not completely separated from the peak (i.e., a step in the slope of the distribution curve that constitutes the peak, where a bulge forms in the middle), and refers to a distribution curve that may or may not have a single maximum value. The "maximum value" refers to the boundary where the slope of the curve in the volume-based frequency particle size distribution changes from positive to negative.

[0012] (Alumina powder) The alumina powder according to this embodiment is made of alumina (Al 2 O 3 ) powder as at least a part of its constituent components, and is preferably made of alumina powder. From the viewpoint of high loading in resin, the alumina powder is preferably spherical alumina. In one embodiment, the alumina powder contains 70 mass % or more, preferably 80 mass % or more, and preferably 90 mass % or more of alumina (preferably spherical).

[0013] The average circularity of the alumina powder is 0.80 or more, preferably 0.85 or more, and more preferably 0.90 or more. When the average circularity is 0.90 or more, it may be 0.90, 0.92, 0.93, 0.94, or 0.95. When the alumina powder has an average circularity of 0.80 or more, the contact area with the resin in the resin composition becomes small relative to the powder weight, making it possible to achieve high loading.

[0014] The average circularity of the alumina powder is a value calculated by the following method. The alumina powder constituting the alumina powder is fixed with carbon tape, and then osmium coating is performed. Then, the particles are photographed at a magnification of 500 to 50,000 times using a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-7001F SHL), and the projected area (S) and projected perimeter (L) of the particles are calculated using an image analyzer (manufactured by Nippon Roper Co., Ltd., product name: Image-Pro Premier Ver.9.3), and the circularity is calculated using the following formula. The circularity is calculated for any 200 particles, and the average value is taken as the average circularity. Circularity = 4πS / L 2

[0015] The alumina powder has a specific surface area of ​​0.23 m2 as measured by the BET method. 2 / g or greater, 0.27m 2 It is more preferable that the specific surface area according to the BET method is 0.27 m 2 / g or more, 0.27m 2 / g, 0.3m 2 / g, 0.6m 2 / g, 0.83m 2 / g, 1.3m 2 In one embodiment, the BET specific surface area may be in a range combining any of the above values ​​as the upper and lower limits. The specific surface area according to the BET method can be measured using a specific surface area measuring device such as "Macsorb HM model-1208" (manufactured by MACSORB). Specific surface area: 0.23m 2 By making it larger than 1 / g, the resin composition containing the alumina powder is likely to exhibit good thermal conductivity and / or good shear adhesive strength. The specific surface area can be adjusted by changing the particle size and ratio of the inorganic oxide powders to be mixed.

[0016] The alumina powder may be produced by mixing commercially available alumina powders having a predetermined particle size distribution, or by blending alumina powders having different particle size distributions. In the case of spherical alumina powder, it may be produced by existing thermal spraying technology. Existing thermal spraying technology is based on, for example, "On Thermal Spraying Collection Technology for Steelmaking Furnaces, Steel Manufacturing Research 1982 No. 310," and involves feeding raw material powder into a high-temperature flame formed with fuel gas such as hydrogen, natural gas, acetylene gas, propane gas, butane, etc., and melting and spheroidizing the powder. One example of a manufacturing device is basically composed of a spheroidizing furnace and a collection device connected to the furnace. The spherical inorganic oxide powder produced in the spheroidizing furnace is air-transported by a blower or the like and collected by the collection device. The spherical inorganic oxide powder is classified as necessary before and / or after collection by the repair device. The spheroidizing furnace body and the transport piping, etc. are preferably water-cooled by a water-cooled jacket method. As the collection device, a cyclone, gravity settling, louver, bag filter, etc. are used. The collection temperature is determined by the amount of heat generated by the amount of combustible gas and the amount of suction by the blower, and is adjusted by the amount of cooling water and the amount of outside air taken in by an equipment in the line, etc. Aluminum hydroxide, alumina, metallic aluminum, etc. are used as raw materials for producing spherical alumina powder. It is desirable to adjust the particle size of the raw material powder to the product particle size in advance, but the particle size can also be adjusted by classification after spheroidization. In addition, spherical inorganic powders having the same composition can be obtained by separating several raw materials with different particle sizes, melting them into spheroids, and then mixing and adjusting them. Mixing can be performed, for example, at room temperature using known equipment such as a blender or mixer.

[0017] By subjecting the alumina powder to a surface treatment using a silane coupling agent or the like, the water absorption rate of the powder can be reduced, the strength of the resin composition can be increased, and further the interfacial resistance between the resin and the powder can be reduced, thereby further improving the thermal conductivity. Examples of silane coupling agents that can be used include vinyltrichlorosilane, vinyltriethoxysilane, vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, β(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycilimethoxypropylmethyldiethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, and the like. Other surface treatment agents that can be used include Zr chelate, titanate coupling agents, and aluminum-based coupling agents.

[0018] (Volume based cumulative 50% diameter D50) The alumina powder has a volume-based cumulative 50% diameter D50 of 10 μm to 70 μm, preferably 10 μm to 65 μm, and more preferably 14 μm to 65 μm. When the volume-based cumulative 50% diameter D50 is 14 μm to 65 μm, it may be, for example, 14 μm, 17 μm, 24 μm, 28 μm, 53 μm, or 65 μm. In one embodiment, the volume-based cumulative 50% diameter D50 may be in a range that combines any of the above values ​​as the upper and lower limits. By setting the volume-based cumulative 50% diameter D50 to 10 μm to 70 μm, the resin composition containing the alumina powder tends to exhibit good thermal conductivity and / or good shear adhesive strength. The volume-based cumulative 50% diameter D50 of the alumina powder can be adjusted by classification, and when a plurality of types of alumina powder are mixed, it can also be adjusted by adjusting the blend ratio of the raw alumina powders.

[0019] (Composition of alumina powder) The alumina powder according to this embodiment may contain two or more types of alumina powder having different D50. In this case, the alumina powder according to this embodiment can be prepared by blending two or more types of alumina powder having different D50. Specifically, for example, by blending alumina powder having a D50 of 20 μm or more and alumina powder having a D50 of 1 μm or more and less than 20 μm in a predetermined amount, alumina powder having a D50 of 10 μm or more and 70 μm or less and a specific surface area of ​​0.23 m 2 An alumina powder having an alumina content of more than 1 / g is obtained. Furthermore, for example, by blending alumina powder having a D50 of 20 μm or more, alumina powder having a D50 of 1 μm or more but less than 20 μm, and alumina powder having a D50 of less than 1 μm in a predetermined amount, it is possible to obtain alumina powder having a D50 of 20 μm or more and a specific surface area of ​​0.23 m. 2 An alumina powder having an alumina content of more than 1 / g is obtained. The amount of each alumina powder is not limited, but may be, for example, 10% by mass to 90% by mass, 15% by mass to 85% by mass, and when it is 15% by mass to 85% by mass, it may be 15%, 35%, 40%, 50%, 60%, 80%, or 85% by mass. In one embodiment, the amount of each alumina powder may be within a range that combines any of the above values ​​as the upper and lower limits. For example, the amount of alumina powder having a D50 of 20 μm or more is preferably 40 to 75 mass%, and more preferably 45 to 70 mass%, based on the total amount of alumina powder. For example, the amount of alumina powder having a D50 of 1 μm or more and 20 μm or less is preferably 25 to 50 mass%, and more preferably 30 to 45 mass%, based on the total amount of alumina powder. For example, the amount of alumina powder having a D50 of 1 μm or less is preferably 5 to 25 mass%, and more preferably 10 to 20 mass%, based on the total amount of alumina powder. In one embodiment, when alumina powder having a D50 of 20 μm or more and alumina powder having a D50 of 1 μm or more and less than 20 μm are blended in a predetermined amount, the blending amount of alumina powder having a D50 of 20 μm or more is preferably 50 to 70 mass%, more preferably 55 to 65 mass%, based on the total amount of alumina powder. When it is 55 to 65 mass%, it may be 60 mass%. When it is 35 to 45 mass%, it may be 40 mass%, based on the total amount of alumina powder. When it is 35 to 45 mass%, it may be 40 mass%. In one embodiment, when alumina powder having a D50 of 20 μm or more, alumina powder having a D50 of 1 μm or more and less than 20 μm, and alumina powder having a D50 of less than 1 μm are blended in a predetermined amount, the blending amount of alumina powder having a D50 of 20 μm or more is preferably 40 to 55 mass%, and more preferably 45% to 55 mass%, based on the total amount of alumina powder. In the case of 45 to 55 mass%, it may be 50 mass%. The blending amount of alumina powder having a D50 of 1 μm or more and less than 20 μm is preferably 25 to 40 mass%, and more preferably 30 to 40 mass%, based on the total amount of alumina powder. In the case of 30 to 40 mass%, it may be 35 mass%. The blending amount of alumina powder having a D50 of less than 1 μm is preferably 5 to 35 mass%, and more preferably 5 to 25 mass%, based on the total amount of alumina powder. In the case of 5 to 25 mass%, it may be 15 mass%.

[0020] In one embodiment, the alumina powder contains 50% by mass of alumina powder having a D50 of 43 μm, 35% by mass of alumina powder having a D50 of 5 μm, and 15% by mass of alumina powder having a D50 of 0.5 μm. This blend results in a powder with a D50 of 24 μm and a specific surface area of ​​0.83 m 2 / g of alumina powder is obtained. In one embodiment, the alumina powder comprises 50% by weight of alumina powder with a D50 of 25 μm, 35% by weight of alumina powder with a D50 of 3 μm, and 15% by weight of alumina powder with a D50 of 0.5 μm. This blend results in an alumina powder with a D50 of 14 μm. In one embodiment, the alumina powder contains 50% by mass of alumina powder having a D50 of 97 μm, 35% by mass of alumina powder having a D50 of 11 μm, and 15% by mass of alumina powder having a D50 of 0.5 μm. This blend results in a powder with a D50 of 53 μm and a specific surface area of ​​0.6 m 2 / g of alumina powder is obtained. In one embodiment, the alumina powder comprises 60% by weight of alumina powder with a D50 of 43 μm and 40% by weight of alumina powder with a D50 of 5 μm. This blend results in an alumina powder with a D50 of 28 μm. In one embodiment, the alumina powder comprises 60% by weight of alumina powder with a D50 of 25 μm and 40% by weight of alumina powder with a D50 of 3 μm. This blend results in an alumina powder with a D50 of 17 μm.

[0021] (Application) The alumina powder according to this embodiment exhibits good thermal conductivity and is therefore suitable for use in applications where thermal conductivity is desired. The alumina powder according to this embodiment exhibits good shear adhesive strength and is therefore suitable for use in applications where good adhesive properties are desired. The alumina powder according to this embodiment exhibits good thermal conductivity and / or good shear adhesion strength, and is therefore suitable for use in applications where thermal conductivity and / or good adhesion are desired. More specifically, the alumina powder according to the present embodiment can be used to manufacture a resin composition comprising the alumina powder and a resin. In one embodiment, the resin composition is preferably an adhesive composition due to its good shear bond strength. That is, the alumina powder can be suitably used to manufacture an adhesive composition. In one embodiment, the alumina powder is an adhesive alumina powder. In one embodiment, the alumina powder is an alumina powder for use in an adhesive composition or for use in an adhesive. Moreover, the resin composition is more preferably an adhesive composition for electronic devices due to its good thermal conductivity and good shear adhesive strength. That is, the alumina powder can be suitably used for the manufacture of an adhesive composition for electronic devices. In one embodiment, the alumina powder is an alumina powder for adhesives for electronic devices. In one embodiment, the alumina powder is an alumina powder for use in an adhesive composition for electronic devices or for use in an adhesive for electronic devices. The alumina powder for adhesives for electronic devices and the adhesive composition for electronic devices can be suitably used for producing adhesives for electronic components of electronic devices, semiconductor sealing materials for electronic devices, adhesives for heat dissipation sheets for electronic devices and adjacent parts, etc.

[0022] [Resin composition] The resin composition according to this embodiment contains the above-mentioned "alumina powder" and a resin. The content of the alumina powder in the resin composition is preferably 80 to 95 mass%, more preferably 83 to 95 mass%, and further preferably 85 to 95 mass%. When the content of the alumina powder is 85 to 95 mass%, it may be 88 mass%. When the content of the alumina powder in the resin composition is 80 to 95 mass%, the resin composition tends to exhibit good thermal conductivity and / or good adhesion.

[0023] Examples of the resin include epoxy resin, silicone resin, urethane resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamide such as polyimide, polyamideimide, polyetherimide, polyester such as polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, and it is preferable to include at least one selected from these.

[0024] When the resin composition is used as an adhesive, it is preferable to use a silicone resin as the resin.

[0025] Examples of silicone resins include thermosetting silicone resins and thermoplastic silicone resins, and among these, thermosetting silicone resins are preferred. Examples of thermosetting silicone resins include those having a skeletal structure such as silane, silicone oligomer, silicone resin, organosiloxane, diorganosiloxane, organopolysiloxane, diorganopolysiloxane, etc., and the skeletal structure has one or more reactive functional groups. The skeletal structure may be a straight chain structure or may have a branched chain. Examples of reactive functional groups include hydroxyl groups, alkenyl groups, epoxy groups, etc. The curing agent is not particularly limited, and known curing agents can be blended. The silicone resin may be a commercially available product or a silicone resin containing two or more commercially available products in a predetermined amount. Commercially available products include, for example, YE5822(A) (manufactured by Momentive Performance Materials, Inc.) and YE5822(B) (manufactured by Momentive Performance Materials, Inc.).

[0026] The resin content in the resin composition is preferably 5 to 20% by mass, more preferably 5 to 17% by mass, and further preferably 5 to 15% by mass. When the resin content in the resin composition is 5 to 20%, the resin composition tends to exhibit good thermal conductivity and / or good shear adhesive strength.

[0027] Other additives may be added to the resin composition as necessary. Examples of such additives include antifoaming agents, leveling agents, rubber-like substances such as polysulfide rubber, acrylic rubber, butadiene rubber, styrene block copolymers, and saturated elastomers, and Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 flame retardants such as phosphorus compounds; colorants such as carbon black, iron oxide, dyes, and pigments.

[0028] (Thermal Conductivity) In one embodiment, the resin composition containing alumina powder and resin is prepared by blending the resin and a filler (alumina powder) in a predetermined ratio and curing the resin at 120°C for 1 hour. A piece of the resin composition is cut out from the resin composition for measurement, and the thermal conductivity measured in accordance with ASTM E 1530 is preferably greater than 2.3 W / m K. By exhibiting a good thermal conductivity of more than 2.3 W / m·K, the resin composition containing the alumina powder and the resin can be suitably used in applications where good thermal conductivity is desired, as described below. The thermal conductivity may be 2.4 W / m·K, 2.5 W / m·K, 2.6 W / m·K, 2.7 W / m·K, or 3.1 W / m·K, and these may be upper or lower limits, or a combination of these may be used.

[0029] In one embodiment, a resin composition containing an alumina powder and a resin is prepared by blending silicone resin:filler (alumina powder) at a ratio of 12:88 (mass%) and curing the resin at 120°C for 1 hour. A piece of the resin composition is cut out from the resin composition for measurement, and the thermal conductivity measured in accordance with ASTM E 1530 is greater than or equal to 2.3 W / m·K.

[0030] (shear bond strength) In one embodiment, the resin composition containing alumina powder and resin is preferably such that the shear bond strength measured based on ASTM D1002 for the aluminum plates bonded by bonding two aluminum plates with a resin composition containing a resin and a filler (alumina powder) in a predetermined ratio and curing the aluminum plates at 120°C for 1 hour is more than 0.23 MPa. By having a shear bond strength of more than 0.23 MPa, the resin composition containing alumina powder and resin can be suitably used in applications where high adhesion is desired, as described below. The shear bond strength may be 0.3 MPa, 0.34 MPa, 0.43 MPa, 0.54 MPa, or 0.64 MPa, and these may be the upper or lower limits, or may be a combination of these ranges.

[0031] In one embodiment, the resin composition containing alumina powder and resin is prepared by laminating aluminum plates with a resin composition having a silicone resin:filler (alumina powder) ratio of 12:88 (mass %) and curing the aluminum plates at 120°C for 1 hour. The shear bond strength measured according to ASTM D1002 is greater than 0.23 MPa.

[0032] In one embodiment, the resin composition containing an alumina powder and a resin has a shear bond strength of 0.3 MPa or more.

[0033] The resin composition can be produced by stirring, dissolving, mixing, and dispersing the above-mentioned materials in predetermined amounts. As an apparatus for mixing, stirring, dispersing, etc., a mortar and pestle machine equipped with a stirring and heating device, a three-roll mill, a ball mill, a planetary mixer, etc. can be used. These apparatuses may also be used in appropriate combination.

[0034] (Application) The resin composition according to this embodiment exhibits good thermal conductivity and is therefore suitable for use in applications where thermal conductivity is desired. The resin composition according to this embodiment exhibits good shear adhesive strength and is therefore suitable for use in applications where high adhesiveness is desired. The resin composition according to this embodiment exhibits good thermal conductivity and / or good shear adhesive strength, and is therefore suitable for use in applications where good thermal conductivity and / or good adhesiveness are desired. In one embodiment, the resin composition is preferably an adhesive composition due to its good shear adhesive strength. Also, the resin composition is more preferably an adhesive composition for electronic devices due to its good thermal conductivity and good shear adhesive strength. The adhesive composition for electronic devices can be suitably used for the manufacture of adhesives for electronic components of electronic devices, semiconductor encapsulants for electronic devices, adhesives between heat dissipation sheets for electronic devices and adjacent parts, etc.

[0035] [glue] The adhesive according to the present embodiment includes the resin composition described above in the section "Resin Composition." As described above, the resin composition may contain additives, and the adhesive may also contain, in addition to the resin composition, the additives exemplified above.

[0036] The content of the resin composition in the adhesive is not limited as long as the adhesive has the desired thermal conductivity and shear adhesive strength required for a specific application, but may be, for example, 95 (mass%) or more, or 99 (mass%) or more.

[0037] The adhesive manufacturing method can be carried out by stirring, dissolving, mixing, and dispersing the resin composition and the other materials in a predetermined amount. As an apparatus for mixing, stirring, dispersing, etc., a mortar and pestle machine equipped with a stirring and heating device, a three-roll mill, a ball mill, a planetary mixer, etc. can be used. These apparatuses may also be used in appropriate combination.

[0038] The adhesive according to the present embodiment contains a resin composition exhibiting good thermal conductivity and good shear adhesive strength, and is therefore preferably used for bonding parts that require good thermal conductivity and good adhesiveness. In one embodiment, the adhesive is an adhesive for electronic devices. More specifically, the adhesive is an adhesive for electronic components of electronic devices, a semiconductor encapsulant for electronic devices, an adhesive for a heat dissipation sheet for electronic devices and an adhesive for adjacent parts, and the like. More specific examples of adhesives for electronic devices include adhesives for bonding between cells and / or modules of batteries for electric vehicles (EVs).

[0039] In one embodiment, an electronic component is provided in which a plurality of components are bonded by the adhesive according to the present embodiment, i.e., the electronic component includes the adhesive according to the present embodiment. Such electronic components tend to exhibit desired thermal conductivity and good thermal management due to the adhesive having good thermal conductivity and good adhesion.

[0040] A non-limiting list of exemplary embodiments and combinations of exemplary embodiments of the present disclosure are disclosed below. [1] The volume-based cumulative 50% diameter D50 is 10 μm or more and 70 μm or less, and the specific surface area by the BET method is 0.23 m 2 / g or more, alumina powder. [2] The alumina powder according to [1], having an average circularity of 0.8 or more. [3] The alumina powder according to [1] or [2], which is for use in adhesives. [4] A resin composition comprising the alumina powder according to any one of [1] to [3] and a resin. [5] The resin composition according to [4], which is used as an adhesive. [6] An adhesive comprising the alumina powder according to any one of [1] to [3] and a resin. EXAMPLES

[0041] The present disclosure will be described in more detail below by showing examples, but interpretation of the present disclosure is not limited to these examples.

[0042] [Examples 1 to 5, Comparative Examples 1 to 3] Spherical alumina powders (raw material) having D50 and specific surface areas shown in Table 2 were mixed according to the composition shown in Table 1 to prepare the alumina powders of Examples 1 to 5 and Comparative Examples 1 to 3. [Table 1] [Table 2]

[0043] The volume-based frequency particle size distribution of the obtained alumina powder was measured using a particle size distribution analyzer (Beckman Coulter, Inc., "LS-13230") under the following pretreatment conditions: refractive index: 1.68, water as the measurement solvent, and ultrasonic homogenizer at 200 W for 60 seconds, using a laser diffraction light scattering method. From the frequency particle size distribution thus obtained, the particle size (D50) corresponding to a cumulative value of 50% was determined.

[0044] The specific surface area of ​​the resulting alumina powder was measured using a specific surface area measuring device such as "Macsorb HM model-1208" (manufactured by MACSORB).

[0045] The average circularity of the alumina powder was measured. The alumina powder constituting the obtained alumina powder was fixed with carbon tape, and then osmium coating was performed. Then, the particles were photographed at a magnification of 500 to 50,000 times using a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-7001F SHL), and the projected area (S) and projected perimeter (L) of the particles were calculated using an image analyzer (manufactured by Nippon Roper Co., Ltd., product name: Image-Pro Premier Ver.9.3), and the circularity was calculated using the following formula. The circularity of any 200 particles was calculated, and the average value was taken as the average circularity. Circularity = 4πS / L 2

[0046] The results are shown in Table 1. In both the Examples and Comparative Examples, D50 was 14 μm to 97 μm. In the Examples, D50 was 14 μm to 53 μm. In the Comparative Examples, D50 was 43 μm to 97 μm. Regarding the obtained alumina powder, the specific surface area of ​​the obtained alumina powder was 0.27 μm to 0.83 μm in the examples, and 0.10 to 0.23 μm in the comparative examples.

[0047] The average circularity of the obtained alumina powder was 0.93 to 0.95 in the examples and 0.92 to 0.95 in the comparative examples.

[0048] The obtained alumina powder was mixed with silicone resin (YE5822(A) and YE5822(B) (both manufactured by Momentive Performance Materials) at a ratio of 90:10 (weight%)) and silicone resin:filler (alumina powder) = 12:88 (mass%), and the resin was cured at 120°C for 1 hour to obtain a resin composition. A measurement piece (30 mm x 30 mm x 3 mmt) was cut out from the resin composition, and the thermal conductivity was measured based on ASTM E 1530. Two aluminum plates were bonded together using a resin composition containing silicone resin and filler (alumina powder) in a ratio of 12:88 (mass%), and the aluminum plates were cured at 120°C for 1 hour. The shear bond strength of the aluminum plates was measured according to ASTM D1002.

[0049] Table 1 shows the measurement results of the thermal conductivity (W / m·K) and shear bond strength (MPa) of the resin compositions containing the alumina powder and silicone resin of Examples 1 to 5 and Comparative Examples 1 to 3. In the examples, the thermal conductivity was 2.4 W / m K or more, and the shear bond strength was 0.3 MPa or more. In other words, the examples were able to achieve both good thermal conductivity and good shear bond strength. In contrast, Comparative Examples 1 to 3 were inferior to the Examples in both thermal conductivity and shear bond strength.

[0050] The alumina powder according to the present disclosure can provide a resin composition exhibiting good thermal conductivity and good shear bond strength. [Industrial Applicability]

[0051] The alumina powder of the present embodiment has good thermal conductivity and good shear adhesive strength, and therefore can be suitably used in applications where thermal conductivity and adhesiveness are desired. Specifically, the alumina powder has industrial applicability, for example, as an adhesive for electronic devices.

Claims

1. The volume-based cumulative 50% diameter D50 is 10 μm or more and 70 μm or less, and the specific surface area by the BET method is 0.23 m 2 / g or more, alumina powder.

2. 2. The alumina powder according to claim 1, having an average circularity of 0.8 or more.

3. The alumina powder according to claim 1, which is for use in adhesives.

4. A resin composition comprising the alumina powder according to any one of claims 1 to 3 and a resin.

5. The resin composition according to claim 4, which is used as an adhesive.

6. An adhesive comprising the alumina powder according to any one of claims 1 to 3 and a resin.

Citation Information

Patent Citations

  • Adhesive resin composition, cured product of the same, and adhesive film

    JP2012077123A